Caracterização clínica e sócio-demográfica dos pacientes idosos internados em hospital terciário e avaliados pelo serviço de interconsulta psiquiátrica - Ribeiro, Ana Elisa Sá Antunes (2018)
The aging process is a reality for most societies and it brings challenges. The elderly patients are more vulnerable to hospitalization and, as a consequence, the impact of this environment on their health. Given the high prevalence of the development of behavioral changes on this population, the psychiatrist plays an important role through Consultation Liaison Psychiatry (CLP). Few studies have evaluated the CLP service and its impact on the elderly inpatient population. Objectives: To characterize the clinical and socio-demographic profile of the hospitalized elderlies who needed CLP, allowing the identification of their characteristics and main psychiatric and clinical disorders. Methods: An observational, descriptive, cross-sectional study was carried out to analyze the CLP requests for elderly patients admitted at Hospital de Base of São José do Rio Preto from 2010 to 2014, using a semi-structured protocol. Data were analyzed by means of a descriptive statistics, with absolute and relative frequencies, as well as Chi-Square test. A value of p <0.05 was considered significant. Results: A total of 204 elderly individuals were evaluated at the CLP service in this period. The mean age was 70.27%, 55.4% were female, 43.6% were married, 92.69% had low schooling and the vast majority did not have paid work (94, 4%). The majority of the evaluations was requested by the medical clinic (38.7%), the main reasons for hospitalization were hypertensive diseases (11.76%). More than a half had a psychiatric history and used psychotropic drugs, especially benzodiazepines. Of these, 24.11% required hospitalization in the past. The most frequent reasons for requesting CLP were: difficulty in dealing with hospitalization (24.74%) and previous psychiatric illness (22.2%). Among psychiatric diagnoses, mood disorders were the most frequent, especially depressive disorders (44.89%). The majority of the patients evaluated by CLP service (60.78%) was treated with pharmacological procedures guided by the team. Conclusion: The increase of aging in association with the elderlies’ fragility makes hospital admissions rates and behavioral changes to this population more prevalent. The elderlies attended by the CLP service have common characteristics with other elderly people evaluated in national and international surveys. CLP can favor a closer relationship between physicians and the multidisciplinary team, thus providing a more appropriate approach and treatment for the elderly patients. The use of a semi-structured protocol for collecting information has added a deeper understanding of this population assisted as well as the medical service provided. Further comparisons can generate greater knowledge, refinement, and should be encouraged.